THE USE OF CROSSWORD PUZZLE IN TEACHING VOCABULARY - Sandra Yulia, - (2010)
The burning issue of the study is about learning vocabulary. Based on the issue, learning vocabulary is important as a basic need to encounter a new language. However, a conventional way of teaching vocabulary does not seem to motivate the students and it even cause lack of vocabulary and fluency. That is why crossword puzzle is proposed as the alternative way to improve students` vocabulary mastery. The aims of the study were to investigate the effect of crossword puzzle treatment in improving students` vocabulary and to investigate the advantages and disadvantages of crossword puzzle based on students' perception. The study used quasi-experimental design with pre-test and post-test non equivalent groups design. The study involved two classes of the fifth grade students of SD Lab School UPI Bandung as the sample. The findings indicated that the crossword puzzle treatment was not significantly effective in improving students` vocabulary mastery. As indicated by a statistical result of posttest score of experimental group (M = 78.67) and control group (M = 73.50), p > 0.05, r = 0.148 indicating a small effect size. Therefore, the null hypothesis is accepted. However, statistical computation results of the posttest of experimental group indicated that there was a higher enhancement of experimental group's vocabulary mastery which could be seen in the pretest score (M= 71.67) and posttest score (M= 78.67), t(23) = - 4.519, p < 0.05, r = 0.544 indicating a large sized effect. In addition, the findings from the interview showed that crossword puzzle is interesting, challenging, and helping the students to absorb the material more easily; however, crossword puzzle also can be confusing and requires a lot of time to be solved. In reference to the result of the study, the conclusion was drawn that the crossword puzzle treatment does not significantly improve students' vocabulary mastery; however, it can encourage students to learn. As the suggestion, the crossword puzzle treatment is recommended to be applied in teaching vocabulary to young learners, and teachers who are applying this technique are suggested to develop more interesting and fun activity in doing the crossword.